Population Pharmacokinetics and Dosing of Milrinone After Patent Ductus Arteriosus Ligation in Preterm Infants. Issue 7 (July 2019) - Hallik, Maarja; Ilmoja, Mari-Liis; Tasa, Tõnis; Standing, Joseph F.; Takkis, Kalev; Veigure, Rūta; Kipper, Karin; Jalas, Tiiu; Raidmäe, Maila; Uibo, Karin; Starkopf, Joel; Metsvaht, Tuuli
Abstract : Objectives: The postoperative course of patent ductus arteriosus ligation is often complicated by postligation cardiac syndrome, occurring in 10–45% of operated infants. Milrinone might prevent profound hemodynamic instability and improve the recovery of cardiac function in this setting. The present study aimed to describe the population pharmacokinetics of milrinone in premature neonates at risk of postligation cardiac syndrome and give dosing recommendations. Design: A prospective single group open-label pharmacokinetics study. Settings: Two tertiary care neonatal ICUs: Tallinn Children's Hospital and Tartu University Hospital, Estonia. Patients: Ten neonates with postmenstrual age of 24.6–30.1 weeks and postnatal age of 5–27 days undergoing patent ductus arteriosus ligation and at risk of postligation cardiac syndrome, based on echocardiographic assessment of left ventricular output of less than 200 mL/kg/min 1 hour after the surgery. Interventions: Milrinone at a dose of 0.73 μg/kg/min for 3 hours followed by 0.16 μg/kg/min for 21 hours. Four blood samples from each patient for milrinone plasma concentration measurements were collected. Measurements and Main Results: Concentration-time data of milrinone were analyzed with nonlinear mixed-effects modeling software (NONMEM Version 7.3 [ICON Development Solutions, Ellicott City, MD]). Probability of target attainment simulations gave a dosing schedule that maximally attains concentration targets of 150–250 μg/L. Milrinone pharmacokinetics was described by a one-compartmental linear model with allometric scaling to bodyweight and an age maturation function of glomerular filtration rate. Parameter estimates for a patient with the median weight were 0.350 (L/hr) for clearance and 0.329 (L) for volume of distribution. The best probability of target attainment was achieved with a loading dose of 0.50 μg/kg/min for 3 hours followed by 0.15 μg/kg/min (postmenstrual age < 27 wk) or 0.20 μg/kg/min (postmenstrual age ≥ 27 wk). Conclusions: Population pharmacokinetic modeling and simulations suggest a slow loading dose followed by maintenance infusion to reach therapeutic milrinone plasma concentrations within the timeframe of the postligation cardiac syndrome. Abstract : Supplemental Digital Content is available in the text.